Effects of gymnastics exercises on executive function in children with autism spectrum disorder aged 6 to 9 years: a pilot study of a randomized controlled trial - Deng, Chenliang; Zhu, Zhimin; Luo, Ganglin; Zeng, Huan; Jiang, Xinwen; Yu, Qiaoyan; Pan, Xiaofei (Frontiers in Psychology, 2025)
ObjectiveTo explore the improvement effects of 12-week gymnastics exercises on executive function (including inhibitory control, working memory, and cognitive flexibility) in children aged 6 to 9 years with autism spectrum disorder (ASD), and to provide a basis for motor interventions in ASD children.Study designA randomized controlled trial (RCT) design was adopted.MethodsTwenty-four ASD children aged 6–9 years from a special school in Chenghua District, Chengdu, were selected and randomly divided into an experimental group (12 cases) and a control group (12 cases). The experimental group received gymnastics exercises (covering movements such as walking, running, crawling, tumbling, and jumping) 3 times a week for 40 min each time, while the control group maintained routine daily activities. Before and after the intervention, the day-night Stroop task, self-ordered pointing task, and Wisconsin card sorting test were used to assess inhibitory control, working memory, and cognitive flexibility, respectively. Independent samples t-tests and paired samples t-tests were performed using SPSS 29.0 to analyze intergroup and intragroup differences.ResultsAfter the intervention, the scores of inhibitory control and working memory in the experimental group were significantly higher than those before the intervention (both p < 0.01), and the score of cognitive flexibility was also significantly improved (p < 0.05). The control group showed a significant difference in working memory (p < 0.05), while there were no statistically significant differences in inhibitory control and cognitive flexibility before and after the intervention (p > 0.05). Intergroup comparison showed that the improvement in each dimension of executive function in the experimental group was better than that in the control group, but there was no significant difference (p > 0.05), which may be related to the short intervention time.Conclusion12-week gymnastics exercises can effectively improve the executive function of 6-9-year-old children with ASD, and can be used as an effective motor intervention for ASD children.